Platelet Transfusion in Dengue: Peril or Protection - Vishwanath Machakanur; MR Savitha; B Krishnamurthy (International Journal of Medical Research and Review, 2015)
Introduction: Dengue is a common vector-borne disease in developing-countries with significant morbidity & mortality. Thrombocytopenia is being a common complication in dengue needs clear guidelines for management. Role of Platelet transfusion in this condition is bit controversial.Method: It was an observational, analytical case-control study based on case record review of children with Dengue with thrombocytopenia(less than 100000/cu mm) with or without minor bleeding, admitted to Cheluvamba Hospital of Mysore Medical College & Research Institute, Mysore, India throughout epidemic period of 2013(June-August). Total of 138 dengue-positive children were studied with respect to two distinct groups with objective to compare the clinical-outcome and platelet-recovery between dengue-positive children with platelet-transfusion (cases) and those without platelet-transfusion (controls). Cases and controls were analyzed for various parameters through SPSS for windows (version 20.0). P-value of < 0.05 was taken as statistically significant.Results: Present study included 36 cases and 102 controls whose baseline-parameters were comparable. ARDS was more common in cases than controls (p=0.000). Duration of platelet recovery, time taken to become afebrile and hospitalization were prolonged in cases as compared with the controls and were statistically highly significant (p=0.000). Another analysis in 11000 to 30000/cu mm platelet count groups revealed the similar results of prolonged duration of platelet recovery, time taken to become afebrile and duration of hospitalization amongs cases as compared with controls.Conclusion: There is no advantage of platelet-transfusion in dengue-positive children with thrombocytopenia with or without minor bleeds. Platelet-transfusion prolongs the duration of platelet-recovery, time taken to become afebrile and hospitalization.